Climate activism favors pro-environmental consumption - Marco Marini; Samuel Nocito (Fondazione Eni Enrico Mattei (FEEM), 2025)
We investigate whether climate activism favors pro-environmental consumption by examining the impact of Fridays for Future (FFF) protests in Italy on second-hand automobile sales in rally-affected areas. Leveraging data on 10 million automobile transactions occurring before and after FFF mobilizations, we exploit rainfall on the day of the event as an exogenous source of attendance variation. Our findings reveal a reduction in both the total number of cars purchased and their average CO2 emissions, with an uptick in the market share of low-emission vehicles and a corresponding decrease in the market share of high-emission counterparts. We test for two potential mechanisms at work: one mediated by an increase in environmental awareness, the other induced by a rational anticipation of future stricter regulations. Empirical evidence suggests that the latter mechanism is generally more pronounced than the former. However, the first channel seems likely to be at work among individuals aged 18-25, a group that is potentially more involved in the FFF movement.
Keywords: D72; D12; Q53; R41; 330; Fridays for Future; climate activism; green consumption; carbon emissions; automobiles